Application of Reactive Oxygen Species-Based Nanomaterials in Dentistry: A Review - Fenglin Liu; Tingting Hong; Jingxian Xie; Xuehui Zhan; Yuehong Wang (Crystals, 2021)
Maintenance of dental health has attracted attention of researchers at present. Various materials have been constructed and applied for curing different dental diseases, although limitation of biocompatibility and safety is still a big challenge. To overcome these limitations, nanomaterials with unique properties are incorporated into various dental treatment materials used in dental applications, including endodontic treatment, periodontal treatment, implant treatment, oral surgery, and restorative treatment, etc. Especially, reactive oxygen species-based nanomaterials equipped with nanoscale properties and reactive oxygen activities can be used as sterilization agents in dentistry, along with being used as good fillers in the dental field. This review concludes the common reactive oxygen species (ROS) nanomaterials and reviews the utilization of ROS in dentistry, highlighting the potential application and safety in clinical treatment. The future prospect will also be proposed to conduct the clinic dental cure.